A Welcome for Chijioke - Ofurum Helen (Macmillian Nigeria, 1983)
Chijioke is eleven years old and has been brought up by his mother in the village. He now has only two photographs, a name and a letter without address. Can he find his unknown father in Lagos.
Keywords: Juvenile Fiction / Adventure / Family